Exploring the Sources of PM10burning-season haze in Northern Thailand using nuclear analytical techniques - Suchart Kiatwattanacharoen (2018)
This study explored the sources of PM 10 in the smoke haze during the traditional burning season in northern Thailand by determining the characteristics of the atomic elements in PM 10 compared to known plant samples. The ambient air was collected from two sites (urban and peri-urban) in the Chiang Mai - Lamphun Basin. This was compared to the characteristics of the leaves from eight agricultural and forest plants predominant in the region: bamboo, grass, teak, yangna, corn, longan, lychee, and rice that were collected and burned in a combustion chamber to collect the resultant PM 10 . The elements - Al, Si, S, Cl, K, Ca, Ti, Cr, Mn, and Fe - were analyzed by PIXE, SEM-EDS, and μ-SXRF. Morphologies of PM 10 particles were analyzed by SEM. The concentrations of the elements in the PM 10 of the ambient air samples correlated highly with the PM 10 from the combustion of teak, yangna, and corn leaves. The results of principal component analysis (PCA), correlations, and morphological characteristics analyzed by SEM also showed that the ambient air PM 10 belonged to the same group as the PM 10 from combustion of teak, yangna, and corn. A HYSPLIT trajectory model indicated that the ambient air PM 10 in the Chiang Mai - Lamphun Basin was derived primarily from hotspots on the Thai-Myanmar border driven by southwest winds, as well as some hotspots in the basin itself. This study has shown that open burning of plant sources, both forest and agricultural, particularly along the Thai-Myanmar border to the southwest, is a primary source of the smoke haze in the Chiang Mai - Lamphun Basin during the dry season.